A review: effects of neurofeedback on patients with mild cognitive impairment (MCI), and Alzheimer’s disease (AD) - Tazaki, Miyako (Frontiers in Human Neuroscience, 2024)
Neurofeedback training (NFT) is a noninvasive method and has been shown to be effective for attention deficit/hyperactivity disorder (ADHD) 1), 2) and various psychiatric disorders 3), 4), 5), 6) . The aim of this paper is to evaluate the effectiveness of NFT for patients with Mild Cognitive Impairment (MCI) and Alzheimer's' disease (AD) or Vascular Diseases (VD), so that we searched research articles from four databases, using the keywords neurofeedback, elderly, MCI, AD, VD, and dementia. As a result, twelve articles were identified regarding the effectiveness of NFT in patients with MCI and AD. Although each study differed in study design, training protocol, and reward and inhibition frequency bands, all were shown to enhance memory, attention, and other cognitive abilities. Additional well-designed, randomized studies with sufficient power are needed to further confirm the effectiveness of NFT.